Pengaruh Minat Kerja, Hard skill, Dan Soft skill Terhadap Kesiapan Kerja Pada Mahasiswa Tingkat Akhir Fakultas Ekonomi Dan Bisnis (FEB) Universitas Dharma Andalas - Yusra, Yusra; Heru Aulia Azman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the Job Interest, Hard skill, and Soft skill on the Job Readiness of Students of the Faculty of Economics and Business, Dharma Andalas University. The population in this study were students at the Faculty of Economics and Business as many as 225 people. The sample in this study was 144 people with the criteria of students who have job readiness. This research is a quantitative research. The instrument used in this study was a questionnaire. The results of the study using multiple linear regression analysis showed that simultaneously there was a significant influence of job interest, hard skills, and soft skills on job readiness and partially job interest had a positive and significant effect on student job readiness, partially hard skills had a positive and significant effect on student job readiness, partially soft skills did not affect student job readiness.